Identification Of Pakistani Truck Visuals And Construction Of Their Meanings Through The Visual Rhetoric Approach - Zahra, Fatima (2020)
Truck art in South Asia has a long history and significance. Most notably, it is one of the most popular and internationally recognised art forms of Pakistan. The reason for the popularity of this art form is the visual portrayal of the cultures of Pakistan’s four regions. Truck art has, therefore, become a way of representing different cultural themes through the enticing nature of its visuals. Such visuals signify the importance of the particular region or area from which the truck originates. In addition, the visuals of the truck are not only aesthetic but also possess communicating power. This research intended to identify the visuals and the persuasion of the visuals to explain in what way the visual elements are functional to the interpretation. This visual-based research is targeted for the construction of visual meanings in terms of the culture of different regions or areas. Thus, the visual has to be explored in each particular aspect associated with it. It is qualitative research, based on a rhetorical study that aims to understand the culturally influenced visuals depicted on trucks. By employing the visual rhetoric theory of artefact proposed by Sonja K. Foss and Aristotle’s rhetorical appeals, this research explores the characteristics, features, and persuasions of these truck visuals as well as their varieties of stylised forms with intrinsic appearances, patterns, placements, and influences of the regions’ cultures. The analysis of the selected truck visuals is based on theme categories that explore different associations of visuals linked with culture.